Self-coincidence of fibre maps - Dold, Albrecht; Gonçalves, Daciberg Lima (Osaka journal of mathematics, 2005)
We study coincidence points for maps f1,f2 : E→B into manifolds such that f1 is homotopic to f2. We analyze the first and higher obstructions to deform f1 away to f2.
Gesehen am 07.09.2022